Strategic vectors of transformational shifts in the national tourism system of Ukraine - Alla Okhrimenko (CES Working Papers, 2017)
The article determines transformational factors, which influence a national tourism system (NTS) of Ukraine and proposes strategical vectors of its development. Research of the NTS as an economic system is a pre-condition for formation of strategic vectors of development. Transformational driving forces principally change scales, components, and proportions between external and internal factors of development of the NTS. Correspondingly, the mentioned processes objectively encourage modernization of the national tourism system and application of innovative managerial methods. The following Strategical vectors of transformational shifts in the NTS were grounded: 1) Safety of tourists and investors; 2) The normative and legislative framework of the NTS development; 3) Development of infrastructure of the NTS component; 4) Human resources development; 5) A marketing policy of the NTS promotion; 6) Ecological and cultural policies. Their implementation will improve efficiency and competitiveness of the NTS and the national economy.
Keywords: 330; national tourism system; transformation; strategic vectors; globalization